Women and religion a sociological analysis - Renavikar, Madhavi D. (Jaipur [u.a.] Rawat Publications, 2003)
Study with reference to Maharashtra, India
Includes bibliographical references (p. [331]-345) and index
Originally presented as the author's thesis (Ph. D.)--University of Pune - Includes index - Includes bibliographical references (p. [331]-345)
Teilw. zugl.: Poona, Univ., Diss.
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Women and religion -- India -- Maharashtra; Hinduism and culture -- India -- Maharashtra; Women -- Social conditions -- India -- Maharashtra; Maharashtra (India) -- Religious life and customs; Hochschulschrift